Proses Pengembangan Media Pembelajaran Interaktif Menulis Skenario Drama Berbantuan Aplikasi Celtx pada Siswa Kelas XI Sekolah Menengah Atas Negeri Satu Hamparan Perak - Fitri Handayani; Rita Rita; Nila Safina (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
The integration of digital tools in language learning has become increasingly essential to support students’ creative writing skills, particularly in drama script composition. This study investigates the development process, feasibility, and effectiveness of interactive learning media for writing drama scripts assisted by the Celtx application among eleventh-grade students at State Senior High School One Hamparan Perak. The study employs a Research and Development approach based on the Four-D development model proposed by Thiagarajan, encompassing the stages of Define, Design, Develop, and Disseminate. The research population consisted of 310 eleventh-grade students, with a sample of 36 students selected for field testing. Data were collected through expert validation, teacher assessments, student responses, and learning outcome evaluations. The findings demonstrate that the developed interactive learning media is categorized as highly feasible, as indicated by assessments from media experts, material experts, teachers, and students, all of which yielded high feasibility percentages. Furthermore, the effectiveness test reveals a substantial improvement in students’ drama script writing skills, with an evaluation score of 90%, classified as highly effective. These results indicate that interactive learning media assisted by Celtx is pedagogically appropriate, practically applicable, and effective in enhancing students’ drama script writing competencies.